Role of Lung Function Monitoring by the Forced Oscillation Technique for Tailoring Ventilation and Weaning in Neonatal ECMO: New Insights From a Case Report - Raffaeli, Genny; Veneroni, Chiara; Ghirardello, Stefano; Lavizzari, Anna; Passera, Sofia; Mosca, Fabio; Cavallaro, Giacomo; Dellacà, Raffaele L. (Frontiers in Pediatrics, 2018)
Abstract Respiratory management during extracorporeal membrane oxygenation (ECMO) is complex. Assessment of lung mechanics might support a patient-tailored ventilatory strategy. We report, for the first time, the use of the forced oscillation technique (FOT) to evaluate lung function during neonatal ECMO to improve the individualization of respiratory support. The patient was a formerly preterm infant at a corrected age of 40 weeks (gestational age 32 weeks) undergoing veno-arterial ECMO for refractory respiratory failure secondary to influenza A (H1N1) pneumonia. We used the FOT as a bedside non-invasive tool for daily monitoring of lung mechanics, from ECMO day 7 (E7) until decannulation. A small-amplitude, 5-Hz oscillatory pressure was overimposed on the ventilation waveform at the airway opening during positive end-expiratory pressure (PEEP) trials. From E6 to E9, lung mechanics changes with PEEP indicated a largely de-recruited and easily over-distendable lung that was not recruitable by applying lung-protective PEEP values. After surfactant and steroid administration, oscillatory reactance (Xrs) values began improving, suggesting a more recruited and pressure-recruitable lung. On E11, despite the lack of improvement in the radiographic appearance of the thorax, the FOT measurements showed a more recruited lung. Weaning from ECMO was started, and the patient was extubated within 48 h. The decannulation was successful, and the patient was extubated within 48 h after ECMO weaning. First-year respiratory and neurodevelopmental follow-up evaluation was unremarkable. This report suggests the potential usefulness of the FOT for monitoring the lung mechanics of ventilated newborns during ECMO to achieve individualized respiratory management. Such tailoring might improve neonatal outcomes and support clinicians with the establishment of a timely and safer weaning approach. These findings need to be verified on a larger population.